Pengaruh Risiko terhadap Profitabilitas Bank yang Terdaftar di Bursa Efek Indonesia - Yulio, Fernando Alvin; Mas'ud, Imam; Wardhaningrum, Oktaviani Ari (Universitas Bina Sarana Informatika, 2024)
Abstract - This study aimed to evaluate the influence of market risk, credit risk, liquidity risk, and operational risk on the profitability of banks listed on the Indonesia Stock Exchange during the period from 2020 to 2022. The chosen timeframe coincided with the emergence of the Covid-19 pandemic, which naturally resulted in a decline in banking profitability and an increase in the risks faced by these banks. The research adopts a quantitative approach, and sample selection employed the purposive sampling method. Secondary data from the Indonesia Stock Exchange were utilized for analysis. Data processing was conducted using EViews 12, involving various tests such as descriptive statistical analysis, classical assumption testing, panel data regression analysis, model testing, and hypothesis testing. The findings of the study reveal that market risk positively affects profitability, while credit risk and operational risk has a negative impact on profitability. Conversely, liquidity risk does not demonstrate a significant effect on profitability. The outcomes of this study hold significance for academic researchers exploring the relationship between risk management practices and bank profitability.Keywords: Bank, Profitability, Risk